Experimental determination of optimal parameters of virus-containing material inactivation by photodynamic method - Melentieva, Khrystyna; Martynov, Artur; Kalinichenko, Svitlana; Minukhin, Valery; Kovalenko, Olga; Antusheva, Tetyana; Ovetchyn, Petro; Kordon, Tetyana (Annals of Mechnikov’s Institute, 2024)
Introduction. To obtain vaccine antigens, strains are usually inactivated either by heating, or by treatment with chemicals: formalin or propiolactone, acetone, alcohol, merthiolate, etc. These substances can enter into a chemical reaction with antigen proteins and change their chemical structure or configuration, forming covalent bonds between toxin proteins and a chemical factor, as a result of which abnormal antigenic determinants appear, increasing the reactogenicity and allergenicity of vaccine preparations. One of the current trends in the problems of improving vaccine preparations is the search for compounds and methods for inactivating pathogens that would be safe and would not lead to the appearance of abnormal antigenic determinants. To date, it has been established that pathogen inactivation systems (SIP) in blood products are effective against numerous bacteria, viruses, and parasites and are widely used in blood product decontamination technologies in transfusion medicine. Such as flavins, which is capable of photomodification, i.e., transfers a charge upon absorption of photons, which mediates cellular signaling or gene expression in endogenous protein complexes, such as light and oxygen sensing domains in bacteria and plants. Materials and methods. The object of research is the polyvalent Piophage® bacteriophage. Reference strains of bacteria (Staphylococcus aureus ATCC 25923 (F-49), Escherichia coli ATCC 25922 (F-50) and Pseudomonas aeruginosa ATCC 27853 (F-51). Bactericidal irradiators (bactericidal wavelength 253.7 nm) were used as an ultraviolet source. As photoinactivators/photosensitizers, a mixture (1:1:1) of solutions of riboflavin, riboflavin menadione sulfate (menadione) and pyridoxine hydrochloride in a concentration of 2×10-4% to 2×10-6% in polysorbate-80 was used ( Fluka, Austria) Determination of the infectious activity of phages was carried out by titration according to Appelman, according to Graz and using the spot test. Results and discussion. According to the results of determining the number of plaque-forming units (PFU/ml) of Piofag®, a significant decrease of this indicator was established when using РS. Extending the irradiation time to 45 minutes led to 100% virulicidal effect in the control as well. Testing for spontaneous reversion of these samples over a three-month period revealed no live virus. The obtained results indicate that ultraviolet irradiation (UV) causes, most likely, local changes in the viral nucleic acid in Piophage® viruses, leading to the replacement of individual bases, thus the reversion of bacteriophage strains that are part of Piophage® does not occur. Conclusion. According to the results of the experiments, the best results regarding the photoinactivation of the virus target material were obtained for 0.02% and 0.01% of the mixture of photosensitizers. UV radiation exposure time at these concentrations ranges from 5 to 15 minutes. For practical use, it is recommended to use 0.02% and 0.01% solutions of riboflavin, pyroxidin, and menadione in a ratio of 1:1:1 in the UFR mode for 5-15 minutes. Keywords: phytoinactivators, bacteriophage, bacteria, vaccines.